Symposium on the Application of Geophysics to Engineering and Environmental Problems 1998 1998
DOI: 10.4133/1.2922515
|View full text |Cite
|
Sign up to set email alerts
|

Relating Cone Penetrometer Test Information to Geophysical Data: A Case Study

Abstract: An analysis of data from a recent experiment at Dover Air Force Base (AFB) has revealed a relationship between soil types determined from the mechanical properties measured by cone penetrometer tests (CPT) and the electrical properties that influence geophysical methods. This correlation connects two distinctly different types of physical properties and provides a petrophysical basis for combining information obtained from CPT and geophysical techniques governed by electrical properties. We observed this relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Published works that relate electrical resistivity with CPT data are therefore rare. Endres and Clement (1998) observed a relationship between soil types determined from mechanical properties measured by cone penetrometer tests (CPT) and electrical properties by using semi-logarithmic crossplots of dielectric permittivity versus electrical resistivity. The analysis revealed that CPT soil types cluster in a systematic manner to form a linear trend from clay-prone to sand-prone lithologies.…”
Section: Introductionmentioning
confidence: 99%
“…Published works that relate electrical resistivity with CPT data are therefore rare. Endres and Clement (1998) observed a relationship between soil types determined from mechanical properties measured by cone penetrometer tests (CPT) and electrical properties by using semi-logarithmic crossplots of dielectric permittivity versus electrical resistivity. The analysis revealed that CPT soil types cluster in a systematic manner to form a linear trend from clay-prone to sand-prone lithologies.…”
Section: Introductionmentioning
confidence: 99%